2006
DOI: 10.1128/jvi.00529-06
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination of Bovine Leukemia Virus-Infected Cells from a Newly Infected Sheep Lymph Node

Abstract: To investigate the early establishment of bovine leukemia virus (BLV) infection, we injected BLV-infected or mock-infected allogeneic cells into the shoulder of sheep in which an efferent lymphatic duct of the draining prescapular lymph node had been cannulated. Rare mononuclear cells acting as centers of BLV infection in culture were present within 4 to 6 days in efferent lymph and within 6 to 10 days in blood. Soon after BLV injection, immunoglobulin M ؉ (IgM ؉ ) and CD8 ؉ cells increased in efferent lymph a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 50 publications
1
7
0
1
Order By: Relevance
“…Several laboratory trials showed that Tax could transform cells in in vitro cultures and being oncogenic in animal models where cells can be transformed when Tax is combined with ha-ras oncogene to produce tumor cells in athymic mice and fibroblasts immortalization coming from rat embryo [24,25]; 2) Viral genome integration process close to highly active cellular genome segments associated with cell division [26]. This is how the Avian Sarcoma Leukosis Virus (ASLV) can integrate in many places of cellular genome, but when there is tumor in the host, the virus has been found upstream of the c-myc cellular gene, which codifies for the Myc proteins implicated in the cellular DNA synthesis control [26,27]. A similar situation happens with MMTV that locates in cellular genome places that induce cellular proliferation by insertional mutagenesis or transcriptional activation of close oncogenes [28,30]; 3) Blocking of tumor suppressors genes and apoptosis activation genes processes [14].…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…Several laboratory trials showed that Tax could transform cells in in vitro cultures and being oncogenic in animal models where cells can be transformed when Tax is combined with ha-ras oncogene to produce tumor cells in athymic mice and fibroblasts immortalization coming from rat embryo [24,25]; 2) Viral genome integration process close to highly active cellular genome segments associated with cell division [26]. This is how the Avian Sarcoma Leukosis Virus (ASLV) can integrate in many places of cellular genome, but when there is tumor in the host, the virus has been found upstream of the c-myc cellular gene, which codifies for the Myc proteins implicated in the cellular DNA synthesis control [26,27]. A similar situation happens with MMTV that locates in cellular genome places that induce cellular proliferation by insertional mutagenesis or transcriptional activation of close oncogenes [28,30]; 3) Blocking of tumor suppressors genes and apoptosis activation genes processes [14].…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…Many studies have detected high sIgM expression levels in the immature B-cells that emigrate from ileal Peyer's patches in sheep (Griebel et al, 1992;Yasuda et al, 2006) and in immature transitional type 1 B-cells in mice models (Cambier et al, 2007;Teague et al, 2007). Furthermore, Fulton et al (2006) detected the emergence of IgM high B-cells only in the blood and not in the efferent lymph after BLV infection in sheep. These reports suggest that the increase in IgM high B-cells in the blood of BLV-infected cattle may be attributable to nonrecirculating immature B-cells derived from either bone marrow or Peyer's patches, which are the primary lymphoid organs responsible for B-cell development and B-cell diversity in cattle and sheep (Yasuda et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that the silenced expression of viral antigens appears to be a strategy for reducing immunogenicity, evading immune surveillance and promoting efficient propagation in BLV-infected cattle. demonstrated that some, but not all, B-cells expressed BLV antigens (Fulton et al, 2006;Gillet et al, 2007;Ikebuchi et al, 2013). Moreover, a silent provirus was integrated into B-cell tumours isolated from BLV-infected sheep and the cell lines derived from these tumours (Merimi et al, 2007a, b;Van den Broeke et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…A similar mechanism of resistance to apoptosis and chronic lymphocytic leukaemia occurs in humans (Pepper et al, 1997). Some authors mention that in the BLV genome, there is no preference for a particular site in the host genome (Murakami et al, 2011), and BLV could integrate itself in active sites associated with the control of cell division (Fulton et al, 2006;Klener et al, 2006). However, Gillet et al (2013) demonstrated that BLV and HTLV-1 have surprisingly similar genomic regions where it is expected that the provirus of both viruses is inserted with a greater likelihood in their respective hosts.…”
Section: Mechanisms Of Cellular Transformationmentioning
confidence: 95%